Creative Mechanisms of Managing Organizational Development in Uncertainty - LEONOV, Yaroslav; ZHELTOBORODOV, Oleksandr; OLKHOVYI, Oleh; PRYKHODKO, Ihor; POBER, Ihor (Theoretical and Practical Research in Economic Fields; Vol 15 No 4 (2024): TPREF Volume XV, Issue 4(32), Winter 2024DO - 10.14505/tpref.v15.4(32).05, 2024)
The research was aimed at identifying innovative strategies and methods aimed at effective management of organizational development in conditions of invisibility. In the process of research were used analytical, statistical and comparative methods. In this article, the key aspects of such management of such an impact on the effectiveness of the functioning of organizations were examined. The results of the research showed that the flexibility of structures is a key aspect of management in conditions of uncertainty, as it allows organizations to react quickly to changes in the environment, adapt to new conditions and make decisions quickly. In addition, it is recognized that strategic risk management is important to ensure the stability of organizations, and innovation management is the key to successful management in conditions of uncertainty. The study examined the role of leadership in stimulating creativity and innovation in solving the problems of invisibility. The importance of the development of culture, which supports creativity and innovation, which is one of the key aspects of management of organizational development in the conditions of invisibility, was highlighted. The significance of cooperation and partnership in the renewal and development of the sports industry, especially in Ukraine, which is vulnerable to the impact of war and pandemic, was examined. The research shows that collaboration between economic sectors and government can accelerate the renewal and development of the sports industry. Consequently, a comprehensive approach to managing organizational development in uncertain conditions was presented, encompassing structural flexibility, strategic risk management, culture, innovation, and stakeholder cooperation.